Cooperatives for prosperity - Mohd. Sulaiman, Aiman @ Nariman; Hingun, Mohsin (Star Media Group, 2020)
On 25 August 2020, the Co-operatives Societies (Amendment) Bill 2020 was tabled for first reading in Parliament with the aim of encouraging the formation of more co-operatives. The Bill does not seem to attract much public attention , probably due to the presence of the more interesting and much anticipated Covid-19 Bill. This is unfortunate as the co-operatives sector has the potential to generate economic growth while doing good. The reform in the Co-operatives Societies (Amendment) Bill 2020 should be taken as the start towards a holistic review of the legal and regulatory framework for cooperative in Malaysia. It is time that we consider a legislative framework for cooperatives societies that will foster the use of cooperatives as a means to ensure inclusive and shared prosperity. At the same time, the legislative framework must also address governance and conflict of interests issues. This requires a relook of the governance and decision-making process of the board and decision-making structure among members.